Efisiensi Prototipe Turbin Savonius pada Kecepatan Angin Rendah - Melda Latif (Jurnal Rekayasa Elektrika, 2013)
Wind energy can be transformed into electrical energy using wind turbine. Based on rotation axis, there are two types of wind turbine, namely turbine with horizontal axis and the one with vertical axis. Turbine with vertical axis has been known with various names that are Darrieus turbine, Savonius turbine and H turbine. This research designed and implemented a prototype of simple Savonius turbine for small scale wind speed. Resistor with resistance of 200 ohm and LED are used as the load. Material of the prototype is alumunium plate, which is light and easy to find. The experiment was conducted at the beach. Permanent magnet synchronous generator was chosen for generating equipment. Voltage resulted by the generator increased as the wind speed increased. The prototype began rotating at wind speed 2.4 m/s. Average efficiency for Y and D connected load are 4.8% and 14.5% respectively.